Virtual Articulators in Contemporary Prosthodontics: A Comprehensive Overview - Boukhris, Hanen; Salah, Kawther Bel Haj; Zidani, Hajer; Bouslama, Ghada; BenYoussef, Souha (Science and Technology: Developments and Applications Vol. 6, 2025)
Aim: This overview aims to explore the role of virtual articulators (VAs) in modern prosthodontics, examining their technological foundation, types, benefits, and challenges in comparison with traditional mechanical articulators. Methodology: A comprehensive review of recent literature was conducted by searching the Medline (PubMed) database and Google Scholar in October 2024, focusing on studies and reviews related to virtual articulators in dentistry. The search, spanning three weeks, identified 24 relevant articles to assess the technological advancements and clinical applications of virtual articulators. Results: Virtual articulators have been shown to enhance the accuracy and efficiency of occlusal surface design, with studies reporting accuracy improvements of up to 20% compared to traditional methods. In clinical scenarios such as full-mouth rehabilitation and complex occlusal corrections, VAs allow for more precise and predictable results, facilitating better patient outcomes. Additionally, VAs improve patient education and communication by providing clear visualizations of treatment plans and supporting interdisciplinary collaboration. However, their adoption is still challenged by high costs, a steep learning curve, and the need for high-quality input data to ensure optimal performance. Conclusion: Virtual articulators offer significant advantages over mechanical articulators, particularly in terms of accuracy, patient satisfaction, and clinical outcomes. Despite the challenges related to cost and training, the integration of VAs is likely to increase as technology advances. Future research should focus on improving the accessibility and affordability of VAs, as well as exploring the potential for integrating artificial intelligence and machine learning to further enhance their functionality and clinical applications.